Perancangan Aplikasi Monitoring Progres Hafalan Al-Qur’an Santri Berbasis Website Dengan Metode Agile (Studi Kasus: Yayasan Sanggar Baca Al-Qur’an) - Mua'mmar; Nasrul Hidayah (OKTAL : Jurnal Ilmu Komputer dan Sains, 2025)
The advancement of technology has brought innovations across various fields, including education. One of these is the Qur’an memorization activities conducted at Yayasan Sanggar Baca Jendela Dunia. So far, the recording of students’ memorization progress has been carried out manually using notebooks, which has several drawbacks, such as data being easily damaged, lost, or difficult to access. Based on these issues, this research aims to design and develop a web-based monitoring system that can digitally record and track students’ Qur’an memorization progress. The system was developed using the Agile methodology, which allows for an iterative and flexible development process according to user needs. The application was built using the PHP programming language and MySQL database, and it is run locally using XAMPP as the server. To ensure the system functions as expected, testing was conducted using both black box and white box methods. The black box testing was used to verify whether the system’s features operate as intended, while the white box testing was conducted to evaluate the program’s logic flow directly through the source code. The results of both testing methods indicate that the system works properly and is capable of supporting the process of recording and monitoring students’ Qur’an memorization progress more efficiently and in a more structured manner.